2019
DOI: 10.1186/s13014-019-1234-z
|View full text |Cite
|
Sign up to set email alerts
|

Is mean heart dose a relevant surrogate parameter of left ventricle and coronary arteries exposure during breast cancer radiotherapy: a dosimetric evaluation based on individually-determined radiation dose (BACCARAT study)

Abstract: BackgroundIntra-individual heterogeneity of cardiac exposure is an issue in breast cancer (BC) radiotherapy that was poorly considered in previous cardiotoxicity studies mainly based on mean heart dose (MHD). This dosimetric study analyzes the distribution of individually-determined radiation doses to the heart and its substructures including coronary arteries and evaluate whether MHD is a relevant surrogate parameter of dose for these substructures.MethodsData were collected from the BACCARAT prospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 29 publications
5
105
0
Order By: Relevance
“…However, it is shown that doses to the substructures such as left ventricle and coronary arteries are better predictors to adverse cardiac events, and mean heart doses do not correlate the substructure doses well. [14][15][16][17] It is, therefore, important to limit doses to heart substructures when they are spared as OARs. There is increase in dosimetric uncertainty due to the nonhomogeneous cardiac motion coupled with the respiratory motion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is shown that doses to the substructures such as left ventricle and coronary arteries are better predictors to adverse cardiac events, and mean heart doses do not correlate the substructure doses well. [14][15][16][17] It is, therefore, important to limit doses to heart substructures when they are spared as OARs. There is increase in dosimetric uncertainty due to the nonhomogeneous cardiac motion coupled with the respiratory motion.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that the doses to the substructures of heart, especially the left ventricle and the left anterior descending artery, were predictive to radiotherapy related cardiac toxicity. [14][15][16][17] The traditional treatment planning constraint, mean dose to whole heart, is not as good a predictor and does not correlate with the doses to the substructures. Therefore, studying the motion of the heart substructures is essential to the safety of cardiac SBRT treatment.…”
mentioning
confidence: 99%
“…While in previous clinical studies, mean heart dose was related to the likelihood of RIHD [12], and the risk of major coronary events in breast cancer patients increased linearly by approximately 4-16% for each 1 Gy in mean heart dose received [6,9,10], other studies have shown that dose to the coronary arteries may also be an indicator of risk of developing coronary artery stenosis, an important aspect of RIHD [73]. Thus, there is a need for irradiation of small segments of the heart in pre-clinical models, which may include key sections of coronary arteries, to accurately predict risk factors and successfully develop interventions in RIHD [64,[74][75][76][77][78]. Partial heart irradiation in small animals may also be used to elucidate ways in which high-dose radiation treatment of segments of the heart can decrease ventricular tachycardia events in patients [79].…”
Section: Target Volume and Methods Of Radiation Delivery In Preclinicmentioning
confidence: 99%
“…Cardiac toxicity has surfaced relatively recently as an issue to be considered in breast radiotherapy (RT), with very basic dose-volumetoxicity relationships having been proposed so far [1], though preliminary data suggest that some cardiac sub-structures may be more problematic than others, particularly highlighting coronary arteries [2,3] and ventricular walls [4]. As recently illustrated by Jacob et al [5], within the framework of the BACCARAT study, the mean heart dose (MHD) is not enough to analyze the correlation between cardiac sub-structures (especially the left anterior descending artery) exposure to therapeutic radiation and resulting toxicity; moreover, the dose distribution in the heart is not homogeneous, neither for traditional tangent irradiation, nor for more recent Intensity Modulated Radiation Therapy (IMRT) approaches [6]. Highest cardiac radiation doses can be observed in the apex and in the apical-anterior segment for tangents and some hot spots > 50 Gy may be applied to some parts of the heart, particularly with tangent treatments, while, with IMRT, typically larger volumes of the heart are exposed to low and intermediate doses.…”
Section: Introductionmentioning
confidence: 99%